PERANCANGAN STANDARD OPERATING PROCEDURE (SOP) SISTEM PENJUALAN DALAM RANGKA MENINGKATKAN AKTIVITAS PENGENDALIAN INTERNAL (STUDI KASUS DISTRIBUTOR BESI BETON DI SIDOARJO) - Dewi, Irina Kusuma; Purwanto, Marini; Oki, Ariston (Widya Mandala Surabaya Catholic University, 2015)
This research is a case study research with object research CV. BJ that specializes in distributor iron concrete for building purposes. CV. BJ categorized in medium size company because it has a fairly large turnover but the operational management of sales still manual and simple. The computer is only used for the purposes of correspondence mailed course. The company had no Standard Operating Procedure (SOP) and its internal control system lacking sufficient. This research aims to analyze the sales systems and designing Standard Operating Procedure sales system in order to increase the activity of internal control of the company. With the design of this SOP, is expected to become a guideline for employees of a company, improving the company's operational activities, and improve the internal control system related to sales. The contents of this study is to identify and analyze the existing problems in the company's sales cycle and improved each of these problems procedures, the evaluation of the organizational structure and internal control and made the preparation of SOP. The data obtained by the organizational structure, job descriptions, systems and procedures of the sales cycle, and documents related to the sales cycle. The methods used in collecting the data used in this study is the interview directly with the owner and several employees, observation, and documentation. This research resulted in the design of Standard Operating Procedure (SOP) sales system as the standard guide the work of the employees so as to increase the activity of the internal control.